2021
DOI: 10.3390/jcm10051133
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Role of Ubiquitination in Melanoma Development and Therapies

Abstract: The ubiquitination system plays a critical role in regulation of large array of biological processes and its alteration has been involved in the pathogenesis of cancers, among them cutaneous melanoma, which is responsible for the most deaths from skin cancers. Over the last decades, targeted therapies and immunotherapies became the standard therapeutic strategies for advanced melanomas. However, despite these breakthroughs, the prognosis of metastatic melanoma patients remains unoptimistic, mainly due to intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 135 publications
1
5
0
2
Order By: Relevance
“…Loss of USP28 in tumour cells is favoured as it results in TP53 protein destabilization, thereby establishing a switch of cell fate, from apoptosis towards mitosis. Hence, USP28 functions as a tumour suppressor in melanoma [55]. In line with these reports, we could not detect a correlation between USP28 and BRAF expression in human skin cancer samples.…”
Section: Discussionsupporting
confidence: 81%
“…Loss of USP28 in tumour cells is favoured as it results in TP53 protein destabilization, thereby establishing a switch of cell fate, from apoptosis towards mitosis. Hence, USP28 functions as a tumour suppressor in melanoma [55]. In line with these reports, we could not detect a correlation between USP28 and BRAF expression in human skin cancer samples.…”
Section: Discussionsupporting
confidence: 81%
“…Loss of USP28 in tumour cells is favored as it results in TP53 protein destabilization, thereby establishing a switch of cell fate, from apoptosis towards mitosis. Hence, USP28 functions as a tumour suppressor in melanoma(41). In line with these reports, we could not detect a correlation between USP28 and BRAF expression in human skin cancer samples.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, studies have reported that NEDD4 serves an essential role in tumor development (33)(34)(35)(36). For example, relevant research findings have shown that abnormal expression of NEDD4 is closely associated with the bioactivity and prognosis of tumors (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the confirmational changes to E3 ubiquitin-ligating enzymes, and E2 (which carries ubiquitin), promote entry to the E3-substrate complex, such that the substrate can be ubiquitinated ( 32 ). Numerous studies have reported that neddylation not only enables a significant increase in the ubiquitination efficiency of proteins to be degraded, but also promotes the degradation of these proteins by the 26S proteasome ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%